Perlindungan Hukum Bagi Peternak Ayam Broiler dalam Pola Kemitraan Inti Plasma dengan PT Ciomas Adisatwa di Kabupaten Kerinci - Maryati Maryati; Putri Anggela Sari (Universitas Batanghari Jambi, 2018)
This research aims to find out and analyze the implementation of legal protection of chicken broiler breeders in partnership pattern core plasma with PT Ciomas Adisatwa Kerinci Regency, to know and analyze problems that happens in relationships the partnerships as well as to know and analyze the efforts that can be made to give legal protection to the breeder the plasma. Ciomas Adisatwa PT is a company that conducts business activities engaged in the breeding of the DOC (Day Old Chickhen) and produces various types of medicines and fodder for livestock. The number of breeders who do partnership with this company is as much as 14 farmers. This study is an empirical juridical research, i.e. research intended to find out how the implementation of legal protection of chicken broiler breeders in partnership with PT Ciomas Adisatwa. in Kerinci; whether it has been in accordance with the legislation in force. Primary data in this study were obtained directly from the results of the research field (field research) by doing the interview PT Ciomas Adisatwa employee, energy coaching and counseling in Dinas Farm District Kerinci, and six (6) people Chicken broiler breeders who partnered with PT Ciomas Adisatwa.. The results showed, legal protection of chicken broiler breeders in partnership with PT Ciomas Adisatwa. in Kerinci haven't fulfilled completely. A right that is already being met with a good breeder is a right to receive guidance about chicken farming from PPL sent by parties to the core. The right to the core of the saprodi have not been fulfilled so well because breeders often get DOC quality bad, feed and drug-obatanpun doubt its quality. The right to obtain a guarantee of marketing is indeed being met but the price that the parties set out the core of the breeder is not satisfactory. Whereas rights that have not been met at all was the right to participate in the making of the agreement. Problems occurring in the implementation of the partnership between rancher PT Ciomas Adisatwa with plasma is a low selling price of production results, Division of excess selling price of no obvious calculation breeder plasma just given potluck, the risk of failed harvest is fully charged to the plasma though the cause of the failed panennya are disease outbreaks, often late harvest and the core does not serve a protest from a breeder. Efforts that can be done to protect the ranchers plasma is by increasing the Government's role in the supervision, control and sustainable construction against the operations of the partnership and gave strict sanctions for parties breaking the rules of partnership.